Where we Live A National Study done by Members of the Inclusive Research Network - Garcia Iriarte, Edurne (Trinity College Dublin; National Federation of Voluntary Bodies, 2010)
The Inclusive Research Network is a group of people with intellectual disabilities from Ireland who do research. We are supported by the National Federation of Voluntary Bodies and the National Institute for Intellectual Disability. We organised 3 research workshops between 2008 and 2009 where we learnt research skills. We came up with the idea of doing a research project on: where people with intellectual disabilities live and how they like it. We decided to do a survey to find out the answers. We did a survey with easy to read questions and pictures about where people live and how they like it. We practised how to ask the questions and how to write the answers. 11 members of the Inclusive Research Network did the survey with 43 people. These members did the survey from June to September of 2009. Staff at the National Institute for Intellectual Disability analysed the answers. We then organised 2 meetings to discuss what we found out: • Most people who did the survey were women and most people were between 20 and 35 years old. • Most people liked where they lived. • Most people lived in towns and with their families. • Most people had their own kitchen, bedroom and bathroom. • Most people had access to taxis and buses. • More than half of the people did not choose who they live with and only half of the people chose where they live. • Half of the people said that they would change things in their homes, only a few would change things about the people they live with, and some would change things about the support they get. Members of the Inclusive Research Network said that more work needs to be done for them to live independently including: more services for people with intellectual disabilities, more control for people over funding, more choices about where and who to live with, more individualised supports, change in families’ attitudes about living independently and more opportunities for people with intellectual disabilities to be heard.
PUBLISHED
Dublin
Keywords: Community living; Human rights; INTELLECTUAL DISABILITY; Inclusive research